1991
DOI: 10.1016/s0735-1097(10)80196-2
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm for restenosis based on cell biology: Clues for the development of new preventive therapies

Abstract: Angioplasty causes substantial injury to the coronary artery intima and media that is unrecognizable by angiography. On the basis of a substantial body of research in oncology and wound healing, it is hypothesized that restenosis is a manifestation of the general wound healing response expressed specifically in vascular tissue. The temporal response to injury occurs in three characteristic phases: inflammation, granulation and extracellular matrix remodeling. The specific expression of these phases in the coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
191
0
19

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 545 publications
(219 citation statements)
references
References 79 publications
9
191
0
19
Order By: Relevance
“…2 Experimental studies have shown that vascular injury induces local expression of mitogens and chemotactic factors, which mediate neointimal lesion formation. This process is characterized in part by the abnormal migration and proliferation of vascular smooth muscle cells in the intima.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Experimental studies have shown that vascular injury induces local expression of mitogens and chemotactic factors, which mediate neointimal lesion formation. This process is characterized in part by the abnormal migration and proliferation of vascular smooth muscle cells in the intima.…”
Section: Discussionmentioning
confidence: 99%
“…Migrating and proliferating smooth muscle cells accompanied by deposition of extracellular matrix and monocyte adhesion and infiltration contribute to the neointimal formation. 2 A substance delivered to the site of injury immediately after angioplasty could have tremendous impact on the restenosis if it could interfere with these processes. Endothelium-derived NO has been shown to antagonize key processes involved in atherogenesis and restenosis.…”
mentioning
confidence: 99%
“…2,3,14,16 Before intravascular ultrasound (IVUS) studies, which changed our perception of restenosis, [21][22][23] we assumed this renarrowing was due to neointimal hyperplasia. 24 For this reason, the investigation of an agent with antioxidant, antichemotactic, and direct antiproliferative effects seemed ideally suited to an atherectomytreated patient population. IVUS studies have since demonstrated that vessel remodelling may account for Ͼ50% of the luminal renarrowing response after DCA, 21,22 which reduces the target for antiproliferative drugs.…”
Section: Appropriateness Of Dca-treated Patients For This Trialmentioning
confidence: 99%
“…The net result of this is the inappropriate migration of vascular smooth muscle cells (VSMCs) from the media to the intima of the damaged vessel where they synthesise extracellular matrix and proliferate, resulting in a gradual reocclusion of the vessel. [4][5][6]with cytotoxic or cytostatic potential, such as herpes simplex virus thymidine kinase (HSVtk), 7 the homeobox gene Gax, 8 the cyclin dependent kinase (cdk) inhibitors p21, p27 and p57 9,10 or constitutively active forms of the retinoblastoma gene product Rb. 11 The number of candidate genes which are expressed solely in VSMCs is limited: the VSMC-specific isoforms of myosin light chain, caldesmon, vinculin and meta-vinculin are produced by alternative splicing of genes that are expressed in many cell types.…”
Section: Introductionmentioning
confidence: 99%